Pengaruh Model Pembelajaran Predict Observe Explain (POE) Berbasis Media Konkret Terhadap Hasil Belajar IPA Siswa Kelas IV MIs Al-Fitrah Kota Kupang - Muhsam, Julhidayat (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to determine the effect of concrete media-based POE learning models on science learning outcomes for fourth-grade students of MIS Al-Fitrah. The research method used is a quasi-experiment. Quantitative data analysis technique based on descriptive statistical analysis. The research design used was the Pretest-Posttest Control Group Design. The instruments used in data collection in this study were questionnaires, observation sheets, and test sheets (pretest and posttest). The instrument used in this research is a test. To determine the validity of a test or learning device, the correlation formula is used, the correlation formula used to measure the validity of the test in this study is the product-moment correlation. The results of the study mean the experimental class was 82.06 and the control class was 70.00. The results of the calculation of the product moment correlation formula show that r-count > r-table, then 0.671–0.995 it is concluded that what was proposed by the researcher is accepted, namely, there is a relationship between the group discussion method and the learning outcomes of class IV students at MIS AlFitrah. Furthermore, the normality test obtained results of 0.377 > 0.05 which indicated that the data was normally distributed, the homogeneity test obtained a value of 0.247 > 0.05, which means that the data is homogeneous, the hypothesis test obtained a value of 0.482 > 0.005 H1 is accepted. From the results of the calculations above, it can be concluded that there is an influence of POE learning media on student learning outcomes in science learning class IV MIS Al-Fitrah.